Estudio de factibilidad para la creación de una empresa de servicios de mensajería y diligencias personales en la ciudad de Santiago de Cali. (2015)
The Feasibility Study for the Creation of a courier company and personal errands in the city of Santiago de Cali, contains in developing various studies seeking to explore the feasibility of creating this type of company. Market research led to the conclusion that there is considerable demand for the services mentioned in the corresponding neighborhoods north of Cali and little supply of them, finding a great interest both in homes and in businesses, to delegate activities messenger in the new company. Through the technical study, the installed capacities were established, designed and used. Furniture and fixtures required by the company for its operation. Ten messengers initially, a manager, a receptionist and an accountant adviser secretary are required. The Administrative Study the kind of society to be established as a corporation Simplified Stock, with two partners, one single capitalist, which contribute 30% cash of the total initial investment and another 70% are financial. Finally, the financial study allowed us to determine that the initial investment in the company amounts to the sum of $ 50 million. The results of the various studies are satisfactory, they were expressed in detail on the content of the project and support the conclusion that the creation of a service company that provides messaging and personal errands in the city of Santiago de Cali is completely feasible and profitable.